Primary Pelvic Tuberculosis That Mimics Ovarian Cancer: A Case Report - Özlem Seçilmiş Kerimoğlu; Berat Berrin Gençoğlu; Aybike Tazegül Pekin; Nasuh Utku Doğan; Setenay Arzu Yılmaz; Çetin Çelik (Gynecology Obstetrics & Reproductive Medicine)
Due to the lack of specific clinical and radiological signs, it is difficult to differentiate genital tuberculosis from ovarian carcinomas and gastrointestinal diseases. Radiological evaluation and increased level of Ca125 may lead to misdiagnosis of disseminated ovarian cancer. A 30 year old women with the complaints of menstrual irregularity, abdominal pain and elevated levels of Ca-125, was evaluated for ovarian cancer. Pelvic magnetic resonance imaging showed minimal ascites fluid and multiple cysts in the right ovary. Intra-operative frozen-section analysis was performed on right paratubal mass and bilateral salphinx. As a result of the frozen-section analysis, granuloma that contained caseous necrosis was reported as tuberculosis. Bilateral salpingectomy, right paratubal mass extirpation and bilateral ovarian tubal tuberculosis. Surgeons should consider genital tuberculosis in the differential diagnosis by avoiding large surgical procedure and intra-operative frozen-section analysis should be done to prevent overtreatment.